Stock return on Scandinavian stock markets and the banking industry: Evidence from the years of financial liberalisation and banking crisis - Ari Hyytinen (Bank of Finland, 1999)
This paper investigates the evolution of the (conditional) volatility of returns on three Scandinavian markets (Finland, Norway and Sweden) over the turbulent period of the past decade, namely the overlapping periods of financial liberalisation, drastically changing macroeconomic conditions and banking crisis. We find that even over this relatively turbulent period volatility is in most cases successfully captured by past volatility and shocks to past volatility, ie by a (symmetric) GARCH process.In each country banking crisis has induced regime shifts in (unconditional) volatility.We also find evidence for cross-country volatility spillovers during the banking crisis episodes.The estimated volatility patterns suggest that even though the volatility of returns was of very high magnitude during the years of banking crisis, developments within the banking industry were not reflected in market uncertainty until all the damage had been done and the severe problems afflicting banks began to be realised in full.
URN:NBN:fi:bof-20140807610
Keywords: 330; GARCH; conditional volatility; banking crisis; volatility spillovers